(untitled) (The Science Post, 2025)
Optimizing outpatient prescriptions is a growing challenge in healthcare systems due to rising drug costs, supply chain disruptions, and the need for equitable access to essential medicines. Smarter drug substitution strategies—such as generic substitution, therapeutic interchange, and algorithm-driven decision support—offer promising solutions to reduce costs while maintaining treatment efficacy and patient safety. This paper examines the role of substitution frameworks in outpatient care, highlights the economic and clinical rationale behind substitution, and discusses digital and policy-based enablers that can standardize the practice. By leveraging artificial intelligence, real-time prescription monitoring, and evidence-based guidelines, outpatient systems can balance cost efficiency with improved health outcomes. The findings underscore that substitution must be carefully integrated into prescribing workflows with consideration for patient trust, regulatory environments, and long-term health system sustainability